The Science of Emotions : A Conversation with Barbara Fredrickson. - Burton, Howard (Toronto : Open Agenda Publishing, 2020)
Why do we smile, laugh and actively seek out personal connections with the people around us? Why does it feel good and what evolutionary purposes do our so-called ""positive emotions"" serve? This book is based on an in-depth filmed conversation between Howard Burton and Barbara Fredrickson, Director Positive Emotions & Psychology Laboratory at UNC Chapel Hill. Topics covered by this extensive conversation include Barbara's work on the science of positive emotions, including her broaden-and-build theory, the undoing effect and upward spirals, while highlighting relevant evolutionary-driven hyp.
Intro -- A Note on the Text -- Introduction -- The Conversation -- I. Psychological Beginnings -- II. Emotions, Scientifically -- III. Positive vs. Negative Emotions -- IV. Positive Psychology Emerges -- V. Broaden and Build -- VI. Emotional Measurement -- VII. The Undoing Effect -- VIII. Taking Charge -- IX. Responses -- X. Personal Flourishing -- XI. Leveraging Positivity -- Continuing the Conversation
Description based upon print version of record.
JSTOR
Keywords: Fredrickson, Barbara -- Interviews; Emotions; Social Psychology; PSYCHOLOGY; Cognitive Neuroscience & Cognitive Neuropsychology; Emotions; SELF-HELP.; Emotions; Interviews